Accuracy of Positive Airway Pressure Device—Measured Apneas and Hypopneas: Role in Treatment Followup. (24th August 2013) - Stepnowsky, Carl; Zamora, Tania; Barker, Robert; Liu, Lin; Sarmiento, Kathleen
Abstract : Improved data transmission technologies have facilitated data collected from positive airway pressure (PAP) devices in the home environment. Although clinicians' treatment decisions increasingly rely on autoscoring of respiratory events by the PAP device, few studies have specifically examined the accuracy of autoscored respiratory events in the home environment in ongoing PAP use. "PAP efficacy" studies were conducted in which participants wore PAP simultaneously with an Embletta sleep system (Embla, Inc., Broomfield, CO), which was directly connected to the ResMed AutoSet S8 (ResMed, Inc., San Diego, CA) via a specialized cable. Mean PAP-scored Apnea-Hypopnea Index (AHI) was 14.2 ± 11.8 (median: 11.7; range: 3.9–46.3) and mean manual-scored AHI was 9.4 ± 10.2 (median: 7.7; range: 1.2–39.3). Ratios between the mean indices were calculated. PAP-scored HI was 2.0 times higher than the manual-scored HI. PAP-scored AHI was 1.5 times higher than the manual-scored AHI, and PAP-scored AI was 1.04 of manual-scored AI. In this sample, PAP-scored HI was on average double the manual-scored HI. Given the importance of PAP efficacy data in tracking treatment progress, it is important to recognize the possible bias of PAP algorithms in overreporting hypopneas. The most likely cause of this discrepancy is the use of desaturations in manual hypopnea scoring.